An expandable web-based platform for visually analyzing basin-scale hydro-climate time series data. (April 2016) - Smith, Joeseph P.; Hunter, Timothy S.; Clites, Anne H.; Stow, Craig A.; Slawecki, Tad; Muhr, Glenn C.; Gronewold, Andrew D.
Abstract: Growing demand from the general public for centralized points of data access and analytics tools coincides with similar, well-documented needs of regional and international hydrology research and resource management communities. To address this need within the Laurentian Great Lakes region, we introduce the Great Lakes Dashboard (GLD), a dynamic web data visualization platform that brings multiple time series data sets together for visual analysis and download. The platform's adaptable, robust, and expandable Time Series Core Object Model (GLD-TSCOM) separates the growing complexity and size of Great Lakes data sets from the web application interface. Although the GLD-TSCOM is currently applied exclusively to Great Lakes data sets, the concepts and methods discussed here can be applied in other geographical and topical areas of interest. Highlights: Solution fulfills documented need in hydrological and resource management communities. Employed visualization paradigm permits easy visual analysis of Great Lakes Data. Data are downloadable for further analysis; Information about data is in application. Novel development model permits significant data and application feature expansion.